2023
DOI: 10.1111/jan.15721
|View full text |Cite
|
Sign up to set email alerts
|

The symptom experience of newly diagnosed Chinese patients with Crohn's disease: A longitudinal qualitative study

Abstract: AimsTo longitudinally explore the symptom experience of Chinese patients with Crohn's disease within the first year following their diagnosis.DesignA longitudinal qualitative study.MethodEighteen newly diagnosed Chinese patients with Crohn's disease were recruited through purposive sampling. Semi‐structured interviews were conducted at four time points: soon after diagnosis, 3, 6 and 12 months post‐diagnosis. Data were collected between January 2021 and February 2022. Conventional content analysis was used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Another study involving newly diagnosed CD patients also revealed three phases of symptom acceptability: difficult to accept, have to accept and be able to accept. 17 Although there are some similarities between the two studies, ours is different in the following aspects. First, Chen’s study focused on the acceptability of symptoms only, whereas our study addressed a broader concept of disease acceptance.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Another study involving newly diagnosed CD patients also revealed three phases of symptom acceptability: difficult to accept, have to accept and be able to accept. 17 Although there are some similarities between the two studies, ours is different in the following aspects. First, Chen’s study focused on the acceptability of symptoms only, whereas our study addressed a broader concept of disease acceptance.…”
Section: Discussionmentioning
confidence: 76%
“… 16 A longitudinal qualitative study explored the phases of acceptability of symptoms in newly diagnosed CD patients. 17 In addition, a supportive environment may act as a catalyst for patient acceptance of the disease. Young adults with IBD and stoma, after an initial phase of anger, began to travel along a predictable path of acceptance and growth as patient education and support services were strengthened and the experiences of stoma management increased.…”
Section: Introductionmentioning
confidence: 99%
“…This study is part of a larger longitudinal qualitative research program aimed at investigating the experiences related to symptoms in individuals with CD. A previous study utilizing the data on symptom perception has been published (Chen & Zhou, 2023). Longitudinal qualitative research involves collecting data at least two different time points from the same participants (Nevedal et al, 2019), and focuses on the lived experiences of changes over time (Audulv et al, 2022;Calman et al, 2013).…”
Section: Designmentioning
confidence: 99%